Wskaźniki niefinansowe w perspektywie kompetencji indywidualnych monitora wartości niematerialnych - Góralski, Bartosz (Non-financial measures of individual competence in intangible assets monitor, 2006)
Intangible assets are influencing managers to change the way of doing business. The processes inside corporations determine their attitude towards employees, product development, service sales and communication with customers. These fundamental changes are affecting strategies, reputation, short and long term decisions. The value drivers are leading toward intangible assets and force managers to develop new methods of their measurement and presentation. The article shows the non-financial indicators of the Individual Competence, which are education, skills, professionalism, experience, culture and projected development of employees who are most valuable assets of a company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 128-134